DETERMINATION OF AGRICULTURAL MACHINERY OPERATORS’ OPINIONS ABOUT THE CABIN COMFORT IN ESKİŞEHİR - Özge Acarbaş Baltacı; Savaş Yapıcı; Ömer Faruk Erol; Zeki Yıldız (Trakya University Journal of Natural Sciences, 2015)
Comfort has a great importance in the interior design of tractor and agricultural machinery cabins. Operators are exposed to muscoskeletal system disorders since they spend long time periods during the day in these vehicles. There is a few work in the literature reporting operators’ opinions about cabin comfort of these machineries. In this study, a questionnaire was conducted in order to get information about agricultural machinery operators’ opinions about the comfort of their vehicles. Tractor cabins and combine harvester machine cabins were selected as machineries. The study was conducted in Eskişehir in Turkey. Questionnaire was composed of four groups of questions and five ordered response levels were used in the Likert's scale. Demographic questions, general questions about the machine, personal evaluation questions and open ended questions were asked to the operators. After the questionnaire completed, collected data were classified according to the machine type. Frequency tables were used to present the results. Visibility and the accessibility were the most satisfied issues for the tractor operators with 55.9% and 55.4% percentages, respectively. Seat comfort has the highest satisfaction degree with 43.7% for the combine harvester operators. Cronbach Alpha reliability coefficient was used for the satisfaction questions in the applied questionnaire. The reliability of the study was high with coefficients of 0.878 and 0.940 for the tractor and combine harvester questionnaires, respectively. This study will support design and development process of new products by considering operator opinions.